Clopidogrel Induced Haematological Dyscrasia: A Case Report - Chowdhury, Abdul Wadud; Siddiq, Amanullah Bin; Islam, AEM Masharul; Saha, Amitav (University Heart Journal, 2010)
Clopidogrel is an analogue of ticlopidine, used for reduction of atherosclerotic events in patients with acute coronary syndrome (ACS), stroke, peripheral arterial disease and for elective percutaneous coronary intervention (PCI). It selectively and irreversibly blocks ADP binding to platelets. Its primary side effect is bleeding. However potentially fatal types of haematological dyscrasia such as aplastic anaemia, neutropenia, thrombocytopenia, pancytopenia may be associated with clopidogrel therapy. A 50 years old diabetic, hypertensive lady with angina was started to treat with clopidogrel along with other anti-ischaemic and anti-hypertensive drugs. Subsequently the patient developed leucopenia and thrombocytopenia after starting of clopidogrel. Five days later her complete blood count returned to normal after withdrawal of both anti platelets. Aspirin was re-introduced with great precaution. Later repeat leucocyte and platelet count were found to be normal. At follow- up 1 month after discharge patient found asymptomatic with normal blood count. To the best of our knowledge, clopidogrel induced haematological dyscrasia was not reported earlier in our country. Key words: Acute coronary syndrome; percutaneous coronary intervention. DOI: 10.3329/uhj.v5i2.4563 University Heart Journal Vol.5(2) July 2009 pp.89-90